Low doses of cannabis extract ameliorate non-motor symptoms of Parkinson’s disease patients: a case series - Ruver-Martins, Ana Carolina; Martinez, Ingrid Andrea Rodriguez; Holla, Vinicius Giesel; Souza, Beatriz Larentis de; Silva, Elton Gomes da; Novoa, Diana Marcela Aragon; Souza-Silva, Eduardo; Araujo, Fabiano Soares; Prediger, Rui Daniel; Nascimento, Francisney Pinto do (Frontiers in Human Neuroscience, 2025)
IntroductionParkinson’s disease (PD) is mainly characterized by motor symptoms including muscle rigidity, resting tremor and bradykinesia. However, the management of the non-motor symptoms represent a relevant clinical challenger in PD. These non-motor symptoms include cognitive and sleep disturbance and there is evidence that cannabinoids may represent alternative and effective treatments for non-motor symptoms of PD.MethodsTherefore, this study addressed the effects of oral treatment with cannabis extract on cognition, insomnia, and daytime sleepiness in six patients with moderate PD. The patients were randomized to receive two different doses of a cannabis extract: THC:CBD 250:28 μg/day (n = 3) or 1000:112 μg/day (n = 3). The assessment of cannabis administration related to the cognitive field was measured by the Montreal Cognitive Assessment test (MoCA test), the insomnia was assessed by the Insomnia Severity Index (ISI), and daytime sleepiness was assessed using the Epworth sleepiness scale (ESS). All clinical evaluations were performed before treatment and at 15, 30, 60, and 90 days of treatment.ResultsThe statistical analysis indicated a significant benefit of the cannabis extract treatment, at dose of 1000:112 μg/day after 60 days of treatment, on insomnia assessed by ISI. Moreover, the statistical analysis of data from ISI and MoCA tests showed a trend toward improvement over time, while no significant effect was observed in the ESS. There were no reports of significant adverse effects during the cannabis extract treatment.DiscussionThese results demonstrate benefits of short-time treatment (60 days) with low doses of cannabis extract on insomnia in PD patients. This study provide novel findings of the potential of combining CBD and THC as safe and effective treatments for non-motor symptoms of PD.